2018
DOI: 10.17504/protocols.io.tpiemke
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

hiC sequencing v1

et al.

Abstract: The golden apple snail (Pomacea canaliculata) is a fresh water snail listed among the top-100 worst invasive species, worldwide and a noted agricultural and quarantine pest that causes great economic losses. It is characterized by fast growth, strong stress tolerance, a high reproduction rate, and adaptation to a broad range of environments.Here, we used long-read sequencing to produce a 440-Mb high-quality chromosome-level assembly for the P. canaliculata genome. In total, 50 Mb (11.4%) repeat sequences and 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
377
0
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 297 publications
(404 citation statements)
references
References 0 publications
20
377
0
7
Order By: Relevance
“…Similar results with miR-29benriched EVs were also obtained by Jahangard et al in rat AD models (Jahangard et al, 2020). On top of miR-29, studies have also shown beneficial effects of miR-21, miR-22, miR-1246, wherein these miRNAs slowed cognitive deterioration in AD mice through regulation of neuroinflammation and synaptic damage (Cui et al, 2018;Cone et al, 2021). With that, in order to optimize miR cargo delivery and, therewith, develop novel AD treatments, one must first understand the intricate connection between progression of AD and exo-miRs (Zeng et al, 2022).…”
Section: Alzheimers' Diseasesupporting
confidence: 83%
“…Similar results with miR-29benriched EVs were also obtained by Jahangard et al in rat AD models (Jahangard et al, 2020). On top of miR-29, studies have also shown beneficial effects of miR-21, miR-22, miR-1246, wherein these miRNAs slowed cognitive deterioration in AD mice through regulation of neuroinflammation and synaptic damage (Cui et al, 2018;Cone et al, 2021). With that, in order to optimize miR cargo delivery and, therewith, develop novel AD treatments, one must first understand the intricate connection between progression of AD and exo-miRs (Zeng et al, 2022).…”
Section: Alzheimers' Diseasesupporting
confidence: 83%
“…152 Therefore, curbing NOx pollution has been a universal issue and various NOx removal technologies have been developed. [153][154] SSOEC with LSM/GDC electrode was adopted to electrochemical catalytic reduction of NO. 155 BaO and Pt were infiltrated to electrodes in order to further improve the catalytic activity.…”
Section: Fuel-assisted Ssoecs and Other Applications Based On Ssoecsmentioning
confidence: 99%
“…It is widely used as a safe, non-invasive, and reliable diagnostic tool to quantitatively analyze cardiovascular autonomic function (Zeki Al Hazzouri et al, 2018). HRV parameters can be obtained through time-domain, frequency-domain and non-linear analyses (Chan et al, 2015). On this basis, researchers can acquire some indicators underlying physiological mechanisms.…”
Section: Introductionmentioning
confidence: 99%